2021
DOI: 10.1021/acs.energyfuels.1c00551
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Oil Recovery Process Using an Organic Alkali–Amino Acid-Based Surfactant System

Abstract: The development of combinatory flooding has evolved over the years to utilize the synergies that come into play upon combining more than one chemical agent in a chemical flooding process. This study focuses on investigating the synergies that exist in combining monoethanolamine (ETA) and sodium cocoyl alaninate (SCA) as an alkali–surfactant (AS) formulation for the enhanced oil recovery process. A conventional formulation made of sodium carbonate (Na2CO3) and sodium dodecyl sulfate (SDS) was used for a compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…56,70 A sharp and clear peak around 535 cm −1 corresponds with Si−O−Al bending vibration, indicating that aluminum oxide is also contained next to silicon oxide. 71,72 The XRD patterns of Ag-NPs/kaolin composite are also shown in Figure 2B. According to previous studies, the diffraction peaks of kaolin found at 2θ = 19.94°, 35.30°, 38.48°, 54.52°, and 62.36°were ascribed to kaolinite.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…56,70 A sharp and clear peak around 535 cm −1 corresponds with Si−O−Al bending vibration, indicating that aluminum oxide is also contained next to silicon oxide. 71,72 The XRD patterns of Ag-NPs/kaolin composite are also shown in Figure 2B. According to previous studies, the diffraction peaks of kaolin found at 2θ = 19.94°, 35.30°, 38.48°, 54.52°, and 62.36°were ascribed to kaolinite.…”
Section: Resultssupporting
confidence: 56%
“…The tiny weak peaks at 2920 cm –1 from the raw kaolin attribute aliphatic hydrocarbon (CH) stretching, indicating an organic impurity, but because of beneficiation, the presence is insignificant. The small peak at 790 cm –1 is attributed to metal impurity bonded with aluminum and hydroxyl (Al-Mg-OH) vibration. , A sharp and clear peak around 535 cm –1 corresponds with Si–O–Al bending vibration, indicating that aluminum oxide is also contained next to silicon oxide. , …”
Section: Resultsmentioning
confidence: 99%
“…The wettability reversal could also occur through alterations of the oil–water or liquid–solid IFT [ 72 ]. ETA, being a weak alkali, would have a weak interaction with the rock; therefore, wettability reversal is not as effective as in the case of inorganic alkalis [ 73 ]. This interaction yields hydrogen bonding between its hydroxyl group and the rock minerals, replacing the polar compounds adsorbed on the rock surface [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the addition of NaBO 2 to CTAB yielded a marginal improvement in the performance of CTAB. The observed synergism is attributed to the combined effect of different mechanisms of wettability alterations by surfactants and alkalis [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increment was to accommodate enhanced and chemical oil recovery mechanisms and varying field cut-offs for net pay zones based on the field development plans and production forecasts. Based on several chemical enhanced oil recovery at field scale, residual oil saturation at 20% is optimal [40]. The overall reservoir water saturation and NMR T 2 LM relationship were established using cross plots.…”
Section: Validating the Developed Approach In Wettability Predictionmentioning
confidence: 99%